2021
DOI: 10.1021/acs.est.1c01010
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Non-targeted Analysis Study of the Prenatal Exposome

Abstract: Recent technological advances in mass spectrometry have enabled us to screen biological samples for a very broad spectrum of chemical compounds allowing us to more comprehensively characterize the human exposome in critical periods of development. The goal of this study was three-fold: 1) to analyze 590 matched maternal and cord blood samples (total 295 pairs) using non-targeted analysis (NTA); 2) examine the differences in chemical abundance between maternal and cord blood samples; and 3) examine the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 52 publications
0
43
0
Order By: Relevance
“…Building on NTA steps from prior studies 4,6,13 , we confirmed and quantified the presence of nine chemicals, some of which have not been previously measured in pregnant people, such tridecanedioic acid, octadecanedioic acid, and tetraethylene glycol, or rarely measured in pregnant people like 4nitrophenol. In addition, a subset of these were moderately to strongly associated with GDM and hypertensive disorders of pregnancy.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Building on NTA steps from prior studies 4,6,13 , we confirmed and quantified the presence of nine chemicals, some of which have not been previously measured in pregnant people, such tridecanedioic acid, octadecanedioic acid, and tetraethylene glycol, or rarely measured in pregnant people like 4nitrophenol. In addition, a subset of these were moderately to strongly associated with GDM and hypertensive disorders of pregnancy.…”
Section: Discussionmentioning
confidence: 61%
“…The selection and confirmation procedures for selection of these chemicals is described elsewhere. 5,6,13 Briefly, in previous NTA studies, 30 matched maternal and cord samples were scanned using HRMS in positive and negative ionization modes identifying suspect features. Detected features were matched to an in-house database and features were then prioritized for MS/MS fragmentation based on the ubiquity of exposure, feature intensity differences across demographic variables, and correlation between maternal and cord samples.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations